2019
DOI: 10.3390/su11133657
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Divergence between Cash Flow and Voting Rights on the Relevance of Fair Disclosure and Credit Ratings

Abstract: This study investigates the effects of governance structure on the relationship between disclosure quality and credit ratings. Firms with greater control-ownership divergence are more likely to pursue their private interests because controlling shareholders obtain the benefit of managerial decision in accordance with controlling interest and they bear the related risk only to the shareholding value. The greater divergence decreases the level of disclosure, thereby increasing the information asymmetry and agenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Chadee et al [31] menyatakan bahwa dampak utama dari penundaan pembayaran terhadap arus kas kontraktor adalah utang yang didapatkan oleh kontraktor tidak besar sehingga sangat berisiko terhadap arus kas proyek untuk menjamin pembayaran kepada subkontraktor dan pemasok. Park et al [32] menyatakan bahwa analisis arus kas membuat keuangan menjadi terstruktur dikarenakan pendanaan yang memadai, hal ini dikarenakan reputasi perusahaan yang bagus sehingga mendapatkan peminjaman yang besar. Abdulghafour [33] menyatakan bahwa pengambilan keputusan dalam suatu proyek akan berdampak terhadap arus kas proyek.…”
Section: Dampak Terhadap Penyelesaian Proyekunclassified
“…Chadee et al [31] menyatakan bahwa dampak utama dari penundaan pembayaran terhadap arus kas kontraktor adalah utang yang didapatkan oleh kontraktor tidak besar sehingga sangat berisiko terhadap arus kas proyek untuk menjamin pembayaran kepada subkontraktor dan pemasok. Park et al [32] menyatakan bahwa analisis arus kas membuat keuangan menjadi terstruktur dikarenakan pendanaan yang memadai, hal ini dikarenakan reputasi perusahaan yang bagus sehingga mendapatkan peminjaman yang besar. Abdulghafour [33] menyatakan bahwa pengambilan keputusan dalam suatu proyek akan berdampak terhadap arus kas proyek.…”
Section: Dampak Terhadap Penyelesaian Proyekunclassified
“…Simultaneously, Park et al (2019) studied the effects of governance structure on the relationship between disclosure quality and credit ratings and found that greater divergence decreased the level of disclosure, thereby increasing the information asymmetry and agency problems, which ultimately might be harmful to firms' sustainability. Hence, examining whether fixed asset revaluation had an impact on the timelines and relevance of information disclosed in financial reporting, Bae et al (2019) revealed that firms with unhealthy financial conditions and a high degree of information asymmetry showed an increase in crash likelihood after fixed asset revaluation.…”
Section: Literature Review Information Asymmetrymentioning
confidence: 99%
“…This refers to the fact that accounting information is deemed relevant for Credit Relevance purposes if it has ability to explain and interpret the creditworthiness of these corporate and predict their likelihood of Default Risks based on financial ratios and indicators derived from financial reporting (Pascan, 2015;Florou et al, 2017). The credit relevance of accounting information lies in its relative ability to predict a company's ability to generate future cash flows being sufficient to meet its financial obligations, provide reliable estimates of assets and liabilities values, and predict the probability of default (Florou et al, 2017;De Lima et al, 2018;Park et al, 2019;Gorgijevska and Gorgieva-Trajkovska, 2019;Dang et al, 2020). In other words, the more relevant the accounting information is to assess a corporate's creditworthiness, the better it is for lenders and investors who rely on this information to make their credit decisions (Pascan, 2015;Florou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%